Comparison of arterial spin labeling registration strategies in the multi‐center GENetic frontotemporal dementia initiative (GENFI). Issue 1 (8th May 2017) - Mutsaerts, Henri J.M.M.; Petr, Jan; Thomas, David L.; De Vita, Enrico; Cash, David M.; van Osch, Matthias J.P.; Golay, Xavier; Groot, Paul F.C.; Ourselin, Sebastien; van Swieten, John; Laforce, Robert; Tagliavini, Fabrizio; et al.
Abstract : Purpose: To compare registration strategies to align arterial spin labeling (ASL) with 3D T1‐weighted (T1w) images, with the goal of reducing the between‐subject variability of cerebral blood flow (CBF) images. Materials and Methods: Multi‐center 3T ASL data were collected at eight sites with four different sequences in the multi‐center GENetic Frontotemporal dementia Initiative (GENFI) study. In a total of 48 healthy controls, we compared the following image registration options: (I) which images to use for registration (perfusion‐weighted images [PWI] to the segmented gray matter (GM) probability map (pGM) (CBF‐pGM) or M0 to T1w (M0‐T1w); (II) which transformation to use (rigid‐body or non‐rigid); and (III) whether to mask or not (no masking, M0‐based FMRIB software library Brain Extraction Tool [BET] masking). In addition to visual comparison, we quantified image similarity using the Pearson correlation coefficient (CC), and used the Mann‐Whitney U rank sum test. Results: CBF‐pGM outperformed M0‐T1w (CC improvement 47.2% ± 22.0%; P < 0.001), and the non‐rigid transformation outperformed rigid‐body (20.6% ± 5.3%; P < 0.001). Masking only improved the M0‐T1w rigid‐body registration (14.5% ± 15.5%; P = 0.007). Conclusion: The choice of image registration strategy impacts ASL group analyses. The non‐rigid transformation is promising but requires validation. CBF‐pGM rigid‐body registration without masking can be used as a default strategy. In patients with expansive perfusion deficits, M0‐T1w may outperform CBF‐pGM in sequences with high effective spatial resolution. BET‐masking only improves M0‐T1w registration when the M0 image has sufficient contrast. Level of Evidence: 1 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;47:131–140.